Manajemen SDM Berbasis Kearifan Lokal dalam Meningkatkan Kinerja Organisasi: Sebuah Kajian Literatur - Cut Muzifatul Ummah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Human resource management (HRM) plays an essential role in determining organizational success in addressing rapid and complex environmental changes. In Indonesia, HRM practices are influenced not only by modern management concepts but also by local wisdom values that have been rooted in social life. Previous studies indicate that integrating local wisdom into HRM practices can strengthen organizational culture, increase employee commitment, build harmonious workplace relationships, and improve organizational performance. However, research on this topic remains fragmented across various sectors, creating a limited comprehensive understanding of the relationship between local wisdom and HRM implementation. This study aims to analyze and synthesize previous studies regarding the implementation of local wisdom-based human resource management and its contribution to organizational performance improvement. The research applies an integrative literature review using a qualitative approach by analyzing relevant journal articles, books, and academic documents. Data were examined through content analysis to identify key themes, compare findings, and develop conceptual synthesis. The results show that local wisdom integration in HRM functions, including recruitment, training, leadership, organizational culture, performance management, and employment relations, positively influences productivity, commitment, collaboration, innovation, and organizational effectiveness. Local wisdom also acts as social capital supporting sustainable competitive advantage. This study provides a conceptual framework for culturally appropriate HRM practices in Indonesia.